Asupan makanan dengan kejadian stunting pada keluarga nelayan di Kota Bengkulu - Emy Yuliantini; Kamsiah Kamsiah; Tonny C Maigoda; Aripin Ahmad (AcTion: Aceh Nutrition Journal, 2022)
The prevalence of stunting in coastal areas in fishing families in Bengkulu city is 29,4%. The potential possessed by coastal areas is not accompanied by the welfare of the lives of the people who occupy low economic strata, including in fulfilling nutrition. This study aimed to determine the relationship between energy consumption, protein, fat, carbohydrates, zinc, and iron with the incidence of stunting aged 1-59 months in fishing families in Bengkulu city. The cross-sectional research method was carried out in 2020 in Padang Serai and Malabro villages, which are fishers' family areas in Bengkulu city. Samples were children under five and mothers respondents with a total of 74. Data on food intake of children under five, obtained through the Food Frequency Questionnaire-Semi Quantitative (SQ-FFQ) and analyzed by nutrisurvey and microtoice to measure height were analyzed by HAZ index. The analysis used Chi-square statistical test. The results showed that there was a relationship between intake of energy, protein, fat, carbohydrates, and zinc in the incidence of stunting under five (p < 0,05), and there was no relationship between iron intake and the incidence of stunting under five (p > 0,05). In conclusion, toddlers with adequate food intake are associated with the incidence of stunting in fishing families. Toddlers need a balanced nutritional intake to prevent stunting through increasing maternal nutritional knowledge.